"Citizenship Cheaters" before the Law: Reading Fraud-Based Denaturalization in Norway through Lenses of Exceptionalism. Issue 1 (3rd March 2023) - Birkvad, Simon Roland
Abstract: For decades, fraud-based denaturalization was hardly used in Norway. In the 2015–2016 "refugee crisis, " however, the right-wing government decided to reinforce efforts to expose "citizenship cheaters." This article asks how this decision emerged, what arguments the government articulated to legitimize this decision, and how parliament responded. I examine the Norwegian case by reworking Schmitt and Agamben's perspectives on exceptionalism. The executive desire to reduce naturalized citizens to "bare life" illustrates Agamben's logic of exception: their potential exclusion is inscribed in law. Yet, the analysis shows that exceptionalism does not necessarily lead to "bare lives": denaturalization was mediated through legal, administrative, and democratic procedures. The opposition submitted proposals to tame the executive's denaturalization powers. In responding to criticism, the government relied on three different arguments to legitimize the decision: (1) moralizing and (2) criminalizing fraud, while simultaneously (3) de-politicizing the decision through hyper-legalism. Such reasoning does not suggest the collapse of law and politics, as Agamben envisions, but rather that states formulate exclusionary politics based on formalistic interpretations of law. The article concludes by problematizing Agamben's claim that we are all equally disposed to sovereign violence. I urge to take seriously social categories of difference in developing a political sociology of exceptionalism.